Huellas de identidad en la danza Choqela: (Puno, Perú) - Gudemos, Mónica; Apaza Ticona, Jorge (Notas de Antropología de las Américas, 2023)
In this paper we address the polysemic nets of identity appropriation of Aimara dances in Puno (Peru). We analyze the tense relationship established between the discourses installed by the structures of political power and the strategies of Aimara communities of the region to sustain these performances as elements of social cohesion. We focus our argumentative observations on the Choqela dance, ritually linked to the vicuña hunting or chaccu.